Peningkatan Keterampilan Komunikasi Saintifik Melalui Group Investigation (GI) pada Calon Guru Sekolah Dasar - Santy Dinar Permata; Ali Mustadi (Universitas Negeri Malang, 2019)
The rapid development of technology and communication in the 21st century requires people to have communication skills, especially in writing. This skill also needs to be mastered by prospective elementary school teachers, in order to be able to teach and provide provisions to students in facing the times. The Group Investigation (GI) learning model is used to improve students' written communication skills related to the science concept. This type of research is a classroom action research with 2 cycles and 4 meetings, with research subjects of 39 elementary school teacher education (PGSD) students. Data collection techniques used in the form of observation. Data were analyzed using descriptive statistics. The results showed an increase in students' written communication skills from pre-action, cycle I, and cycle II. Improvement of students' written communication skills is shown through the results of the N-gain score test in pre-action up to the second cycle of 0.36 with the medium category. The indicator of research completeness also shows that 82% or 32 students have experienced an increase with an average score of 67.6 and are categorized in the skilled to very skilled categories. Perkembangan teknologi dan komunikasi yang sangat cepat di abad 21, mengharuskan masyarakat memiliki keterampilan komunikasi, khususnya secara tertulis. Keterampilan ini juga perlu dikuasai oleh calon guru sekolah dasar, agar mampu mengajarkan dan memberikan bekal kepada siswa dalam menghadapi perkembangan zaman. Model pembelajaran Group Investigation (GI) digunakan untuk meningkatkan keterampilan komunikasi tulis mahasiswa terkait konsep IPA. Jenis penelitian yang digunakan adalah penelitian tindakan kelas dengan 2 siklus dan 4 pertemuan, dengan subjek penelitian 39 mahasiswa PGSD. Teknik pengumpulan data yang digunakan berupa observasi. Data dianalisis menggunakan statistik deskriptif. Hasil penelitian menunjukkan adanya peningkatan keterampilan komunikasi tulis mahasiswa dari pratindakan, siklus I, dan siklus II. Peningkatan keterampilan komunikasi tulis mahasiswa ditunjukkan melalui hasil uji N-gain score pada pratindakan hingga siklus II sebesar 0,36 dengan kategori sedang. Indikator ketercapaian ketuntasan penelitian juga menunjukkan sebanyak 82% atau 32 mahasiswa telah mengalami peningkatan dengan nilai rerata 67,6 dan tergolong dalam kategori terampil hingga sangat terampil.